2011
DOI: 10.1016/j.ophtha.2011.06.032
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Associated with Childhood Strabismus

Abstract: Objective To investigate risk factors associated with esotropia or exotropia in infants and young children. Design Population-based cross-sectional prevalence study. Participants Population-based samples of 9970 children ages 6 to 72 months from California and Maryland. Methods Participants were preschool African-American, Hispanic, and non-Hispanic white children participating in the Multiethnic Pediatric Eye Disease Study and the Baltimore Eye Disease Study. Data were obtained by parental interview and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
82
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(94 citation statements)
references
References 63 publications
4
82
0
Order By: Relevance
“…30 Data from the Multi-Ethnic Pediatric Eye Disease Study (MEPEDS) and the Baltimore Pediatric Eye Disease Study (BPEDS) also demonstrated that after multivariate analysis, infants with a GA <33 weeks had a considerably higher odds (OR=2.48 ([CI, 1.17–5.25]) for development of strabismus relative to those with GA of ≥33 weeks. 43 Unfortunately, neither study considered BW. Since it is known that BW is correlated with GA, it is possible that the findings observed in these analyses may actually be more attributable to BW than GA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…30 Data from the Multi-Ethnic Pediatric Eye Disease Study (MEPEDS) and the Baltimore Pediatric Eye Disease Study (BPEDS) also demonstrated that after multivariate analysis, infants with a GA <33 weeks had a considerably higher odds (OR=2.48 ([CI, 1.17–5.25]) for development of strabismus relative to those with GA of ≥33 weeks. 43 Unfortunately, neither study considered BW. Since it is known that BW is correlated with GA, it is possible that the findings observed in these analyses may actually be more attributable to BW than GA.…”
Section: Discussionmentioning
confidence: 99%
“…Well-recognized risk factors for strabismus include anisometropia and refractive error 11,12 , genetics 13,14 , older age of parents 1,15 , maternal cigarette smoking during pregnancy 15,16 , neurodevelopmental impairment 17,18 , low APGAR (Appearance, Pulse, Grimace, Activity, Respiration) scores 19 , craniofacial and chromosomal abnormalities 20,21 , in utero toxin exposure 22 , retinopathy of prematurity (ROP) 23,24 , and caesarian delivery 5,25 . For children who are born premature, there is debate in the literature regarding two other potential risk factors, birth weight (BW) and gestational age (GA) 26,27,28,29 (eTable 1) 1,2,15,2325,2933 .…”
mentioning
confidence: 99%
“…13,14,17,48 The rationale for retinal birefringence screening with the PVS device is quite different. Namely, it is a simple, quick test that can be used to refer only affected children to eye care professionals or screen children at regular intervals in a primary care setting to provide early and accurate identification of those who develops trabismus or amblyopia.…”
Section: Discussionmentioning
confidence: 99%
“…For vision, the incidences of problems such as myopia, hyperopia and astigmatism do not appear to be greater than reported in US preschool children. 54, 55 However, the high rate of strabismus (16.9%) in international adoptees compared to preschool children in the UK (2.1%) 56 and US (2.4%) 57 is of great concern since esotropia is one of the most robust predictors of decreased visual acuity in pre-school children. 58 Our identification of a high rate of strabismus is supported by Gronlund, et al, who reported a prospective study of 72 of 99 children in Western Sweden who were adopted from Eastern Europe during 1993–1997, comparing them to an age- and sex-matched reference group.…”
Section: Discussionmentioning
confidence: 99%
“…64 Low birth weight, common among international adoptees 20, 36 but not analyzed in this study due to limited data, is a risk factor for vision problems, particularly strabismus. 56, 57, 65 Middle ear disease is a leading cause of hearing loss in children, 66 as reflected in the MnIAP cohort where recurrent ear infections post-adoption was identified as an independent risk factor. Duration of institutionalization is an independent risk factor for hearing problems, most likely mediated via high rates of respiratory illness in congregate care settings 36, 67 coupled with overall medical, nutritional and social neglect.…”
Section: Discussionmentioning
confidence: 99%